PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN TRADISIONAL ENGKLEK PADA KELOMPOK A DI RA HIDAYATUL MUBTADIIN SIPRING PAGELARAN-MALANG - Nur Laila; Nurhayati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2019)
The purpose of this research is to describe the traditional game of crank to improve children's cognitive abilities, to describe how to improve children's ability to recognize the symbol of children numbers 4-5 years old at RA Hidayatul Mubtadiin Pagelaran. The research design used was Classroom Action Research using two cycles. Data collection techniques used observation, interviews and documentation. The results of the study were shown to have an increase in cognitive abilities in group A children at each cycle. The percentage of completeness data obtained 53.3% in cycle 1, and is increasing at the end of cycle 2 that is equal to 86.6%. Thus, an increase in the ability to recognize the symbol of numbers through the game of crickets in children aged 4-5 years from cycle 1 to cycle 2 with a difference of 33.3%. Based on the results of data analysis, it was concluded that cognitive abilities had increased significantly. Seen from the final results states that the concept of traditional cricket game has the criteria of interest, ease and suitability in the learning process.